Non-fiction cinema of independent Ukraine - Marchenko, Serhiy (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article covers the thematic and genre diversity of non-fiction cinema in Ukraine, which following the country’s regaining its independence in 1991, launched a reflection on previously hushed-up topics that were prohibited or covered in a tendentious manner in the Soviet period. The number of films and TV series grew, and the ideological gap between film artists and political elites (partly pro-Russian) resulted in their mass distribution being prevented. This was especially evident in the several-year delay and limits placed on showing the long-awaited series “Unknown Ukraine. Essays of Our History” (1993, NKU-Kyivnaukfilm, 144 films). Quantitative and qualitative changes in this type of cinema over the last three decades are analyzed in this article, presenting periods of its ups and downs, which are synchronized with changes in political processes in Ukraine. It shows how after the mass protests of the Euromaidan Revolution in 2014 and the beginning of the Russian-Ukrainian war, the number of such films increased significantly, providing a considerable informative and educational impact.